2012
DOI: 10.1590/s0100-29452012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Conservação pós-colheita de guavira (Campomanesia sp.)

Abstract: RESUMO -Este trabalho foi realizado com o objetivo de avaliar a conservação pós-colheita de guavira (Campomanesia sp.), em função da utilização de 1-MCP e de atmosfera modificada passiva, além do armazenamento à temperatura ambiente e a 11°C. Os frutos foram colhidos no ponto de maturidade fisiológica, subdivididos em parcelas e submetidos à aplicação de 1-Metilciclopropeno (1-MCP) (700 ηL.L -1 /12horas) e à atmosfera modificada passiva por meio do uso de embalagem plástica. Foram realizadas análises de perda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
8
0
7
Order By: Relevance
“…(Campos et al, 2012) and 288 mg GAE per 100 g FW for strawberry (Fragaria x ananassa) (Crecente-Campo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…(Campos et al, 2012) and 288 mg GAE per 100 g FW for strawberry (Fragaria x ananassa) (Crecente-Campo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although showing great potential, they have mostly been exploited in an extractivist manner, since the fruits are not well-known or appreciated outside the Savannah region (FINCO et al, 2012). Thus, the regional consumption of food with potential nutritive and functional value can be encouraged through the use of post-harvest technologies which increase the shelf life of these fruits, providing new products and generating added value (CAMPOS et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits are consumed in nature or processed as juicy and ice cream (Baviati et al, 2004) and are appreciated by population considering the high Vitamin C content (Oliveira et al, 2011) and the medicine proprieties (Fernandes et al, 2014). Studies at refrigerate conditions (Campos et al, 2012) and modified atmosphere (Scalon et al, 2012) shown important to preserve the postharvest quality under 15 days of storage.…”
Section: Introductionmentioning
confidence: 99%